A sectional impression tray technique for an oral submucous fibrosis patient with limited mouth opening - Sowmya Mangalore Kumar; Prasad D Krishna; Rushad Hosi Nariman (Wolters Kluwer Medknow Publications, 2014)
Oral submucous fibrosis (OSMF) is a precancerous condition. It causes difficulty in swallowing, chewing and speaking due to the presence of microstomia. Limited mouth opening is considered as a hindrance in prosthodontic rehabilitation of a patient. Special impression procedures and techniques should be considered for making an impression in such cases. This article describes the fabrication of a split impression tray to make a secondary impression of an edentulous patient having OSMF.